1992
DOI: 10.1111/j.1471-4159.1992.tb11358.x
|View full text |Cite
|
Sign up to set email alerts
|

D1 Dopamine Receptor Activation of Multiple Transcription Factor Genes in Rat Striatum

Abstract: Recent studies have shown that dopamine receptor agonists induce expression of Fos-like immunoreactivity in rat striatal neurons. The protooncogene c-fos belongs to a family of immediate early genes that are rapidly induced in fibroblasts by growth factors. In light of previous findings that several immediate early gene mRNAs that encode proven or putative transcription factors are differentially regulated by neuronal stimulation in vivo, we have examined the effect of dopaminergic agents on mRNA levels of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(72 citation statements)
references
References 37 publications
5
64
0
2
Order By: Relevance
“…We did not determine which of these two pathways showed differential c-fos induction by the cocaine challenge after the running-wheel training. Psychostimulant-induced immediate-early gene expression is principally mediated by D1 receptors (Graybiel et al, 1990;Young et al, 1991;Cole et al, 1992;Steiner and Gerfen, 1995;Drago et al, 1996;Moratalla et al, 1996) in interaction with glutamate input (see Berke and Hyman, 2000). Moreover, double-labeling studies demonstrated that psychostimulants induce c-fos predominantly in direct Correlation coefficients (r) for correlations between increases in ambulation and c-fos (left) or substance P mRNA levels (right) in 26 striatal sectors are shown for rats that received a cocaine challenge (25 mg/kg) 24 h after the 1-, 2-or 8-day wheel training (RC/C and LC/C groups pooled).…”
Section: Evidence For Molecular Changes In the Direct Pathway Associamentioning
confidence: 99%
“…We did not determine which of these two pathways showed differential c-fos induction by the cocaine challenge after the running-wheel training. Psychostimulant-induced immediate-early gene expression is principally mediated by D1 receptors (Graybiel et al, 1990;Young et al, 1991;Cole et al, 1992;Steiner and Gerfen, 1995;Drago et al, 1996;Moratalla et al, 1996) in interaction with glutamate input (see Berke and Hyman, 2000). Moreover, double-labeling studies demonstrated that psychostimulants induce c-fos predominantly in direct Correlation coefficients (r) for correlations between increases in ambulation and c-fos (left) or substance P mRNA levels (right) in 26 striatal sectors are shown for rats that received a cocaine challenge (25 mg/kg) 24 h after the 1-, 2-or 8-day wheel training (RC/C and LC/C groups pooled).…”
Section: Evidence For Molecular Changes In the Direct Pathway Associamentioning
confidence: 99%
“…Striatal dysfunction is implicated in a variety of neuropsychiatric disorders (37)(38)(39), including drug addiction (40,41). Genes induced in striatal neurons by systemic psychostimulant administration include c-fos (42,43), zif 268 (44) and homer 1a (45,46). Such gene induction is principally mediated by D 1 -like receptors; however, D 2 -like receptors additionally modulate such effects (47,48).…”
Section: Introductionmentioning
confidence: 99%
“…Such gene induction is principally mediated by D 1 -like receptors; however, D 2 -like receptors additionally modulate such effects (47,48). Notably, psychostimulantinduced gene regulation is abolished by D 1 receptor blockade (42,44,49,50), or by targeted deletion of D 1 receptors (51-54).…”
Section: Introductionmentioning
confidence: 99%
“…In L-DOPA treated animals (both dyskinetic and nondyskinetic) 42 genes were more highly expressed and 95 less highly expressed when compared with untreated parkinsonian controls (Figure 2 B and 2 C; total genes enclosed within both of the lowermost circles). A subset of genes was selected for further examination, based on their role as transcription factors and immediate early genes, known to be activated in response to dopamine receptor stimulation (Cole et al, 1992;Moratalla et al, 1992;Berke et al, 1998). Expression was examined in RNA from the individual rats in the RNA-seq experiment using RT-qPCR to verify patterns observed in the RNA-seq dataset and the results compared with the RNA-seq counts (Figure 3).…”
Section: Rna-seq Profilesmentioning
confidence: 99%
“…An adjusted p-value of 0.05 was used as the threshold for significance (Cameron et al, 2013). A subset of genes were selected for further examination, based on their role as transcription factors and genes known to be activated soon after dopamine receptor stimulation (Cole et al, 1992;Moratalla et al, 1992;Berke et al, 1998). These genes: Arc, Egr1, Fos, Junb, and Nr4a1, were examined using TaqMan gene expression probe sets (Life Technologies) to confirm gene expression patterns observed in the RNA-seq dataset.…”
Section: Sacrifice Rna Extraction and Sequencingmentioning
confidence: 99%